Invasive bladder cancer – urine diversion in own material - Tkocz, Michał; Duda, Wiesław; Szedel, Andrzej; Kawecki, Jan; Kupajski, Maciej; Ziaja, Damian (Contemporary Oncology/Współczesna Onkologia, 2008)
Background: Radical cystectomy is the contemporary method of choice to treat invasive bladder cancer and the ileal conduit is one of the most commonly used for urine diversion. The aim of this study is to evaluate the patients under the treatment as well as factors which influence the choice of urine diversion with patients who have undergone cystectomy because of invasive bladder cancer. Material and methods: Cystectomy was carried out among 154 patients suffering from invasive bladder cancer. 17.5% of patients under the treatment had an intestinal bladder created. 59.1% of patients were treated with an ileal conduit as the way of urine diversion, while with 22.7% of patients under the treatment it was possible only to transplant the ureters to the skin. Results: The histopathological exami-nation of the postoperative material showed the presence of TCC in 142 patients. In 10 cases it was plano-epithelial cancer, in 1 case adenocarci-noma and in 1 case undifferentiated cell carcinoma. Within the TCC group the degree of clinical progression T2 was found in 77 patients (54.2%), T3 in 54 patients (38.1%), T4 in 11 patients (7.7%). In the T2 phase G1-G2 there were 35 patients (45.4%), in the T2 G3 stage there were 45 patients (54.5%). In the T3 G2 phase there were 7 patients (13%) while in the T3 G3 phase there were 47 patients (87%). The degree of clinical progression of T4 was found in 11 patients. All patients in this group featured the presence of cancer of the G3 degree of histological malignancy. The presence of perivesicular infiltration in the CT (computed tomography) was demonstrated in 57 patients (37%). During the cystectomy changes suspected of perivesicular tissue infiltration were demonstrated in 52.6% of the operated patients, while the presence of macroscopically-changed lymphatic nodes in the obturator region and iliac vessels was demonstrated in 37.6% of the operated patients. Conclusions: The progression of the malignant disease in the group in question and the psychological state of the patients determined the choice of kind of urine diversion using the ileal conduit. This method was applied in 59.1% of patients. In 22.7% of cases it was possible only to create the uretero-cutaneous anastomosis and only 17.5% of patients were qualified for the creation of an intestinal bladder using one of the methods available.